Why Zambia failed. Issue 4 (6th November 2014) - BARTON, STUART JOHN
Abstract: Daron Acemoglu, James Robinson and others are explaining divergent economic histories with qualitative measures of institutional quality – including Acemoglu and Robinson's popular inclusive/extractive dichotomy. While quantitative studies have sort to confirm these links using econometric proxies, few empirical accounts have shown how these proxies, or indeed the institutions they seek to represent actually influenced economic growth. This study helps fill that gap by testing whether evidence in Zambia's post-colonial history supports a proposed econometric link between its institutional quality and its slow economic growth. Support for this link is found in foreign investors' interpretation of declining institutional constraint on Zambia's President as the potential for increased policy volatility, and as such an economic inducement to delay critical investment to Zambia's capital constrained economy. These findings add weight to the institutional argument in general, as well as present one concrete example in history of a mechanism through which institutional quality affected economic growth.